2017
DOI: 10.1111/ejn.13575
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic vs. deterministic fiber tracking and the influence of different seed regions to delineate cerebellar‐thalamic fibers in deep brain stimulation

Abstract: This study compared tractography approaches for identifying cerebellar-thalamic fiber bundles relevant to planning target sites for deep brain stimulation (DBS). In particular, probabilistic and deterministic tracking of the dentate-rubro-thalamic tract (DRTT) and differences between the spatial courses of the DRTT and the cerebello-thalamo-cortical (CTC) tract were compared. Six patients with movement disorders were examined by magnetic resonance imaging (MRI), including two sets of diffusion-weighted images … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 44 publications
(73 reference statements)
2
48
1
Order By: Relevance
“…Additionally, the diffusion data used from the human connectome project is superior in quality to most images acquired during clinical routine and while a population-based average tract might neglect individual neuroanatomic aberrations, it might also be less prone to tracking errors which have been shown to occur when identifying individual DRTTs. 15 Most importantly, the average deviation of individual patient DRTTs from our population-based DRTT was within the range of image accuracy (see supplementary material). We employed probabilistic fiber tracking, as it might be better in detecting the DRTT than the deterministic algorithms embedded in commercially-available stereotactic planning software.…”
Section: Discussionmentioning
confidence: 53%
“…Additionally, the diffusion data used from the human connectome project is superior in quality to most images acquired during clinical routine and while a population-based average tract might neglect individual neuroanatomic aberrations, it might also be less prone to tracking errors which have been shown to occur when identifying individual DRTTs. 15 Most importantly, the average deviation of individual patient DRTTs from our population-based DRTT was within the range of image accuracy (see supplementary material). We employed probabilistic fiber tracking, as it might be better in detecting the DRTT than the deterministic algorithms embedded in commercially-available stereotactic planning software.…”
Section: Discussionmentioning
confidence: 53%
“…Note, however, that our data sample for tremor symptoms was limited and that tractography is less sensitive in detecting decussating than ipsilateral fibers. 28 Similarly, our data showed no contingency between effectiveness for rigidity alleviation and DRTT targets. Instead, rigidity alleviation was associated with ascending brainstem (ML, FAL, BIC) and intralaminar thalamic fibers (f-H1, IML).…”
Section: Cerebellothalamocortical Pathwaysupporting
confidence: 48%
“…Tractography based on 64 orientations may be superior to fewer orientations in detecting the DRTT and adjacent fiber tracts 28 and may result in more reliable and less noisy estimates of diffusion parameters. Instead of examining tractographies on a standardized template brain, we examined the individual tractograms on patient-specific images.…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Approaches can be deterministic, like the one used here, or probabilistic. Recently, however, Kupper et al (), Khalsa, Mayhew, Chechlacz, Bagary, and Bagshaw (), Schlaier et al () and Sarwar, Ramamohanarao, and Zalesky () showed that deterministic tractography often agrees with probabilistic tractography. While this may be considered convincing evidence, studies like (Jeurissen, Leemans, Jones, Tournier, & Sijbers, ) render the need for future studies to address this comparison in more detail.…”
Section: Discussionmentioning
confidence: 99%